THE EFFECT OF STRATEGIC DIRECTION IN ENHANCING THE ROLE OF SOCIAL RESPONSIBILITY THROUGH ORGANIZATIONAL PROWESS IN JORDAN SERVICES MINISTRIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Global competitiveness and the changing surrounding circumstances have made institutions more aware and vulnerable to adopting change continuously, as this requires active participation from every level of the organization, and to achieve the goal of the study, the comparison method was adopted, and the results of previous studies showed that there is a positive relationship between strategic orientation and social responsibility through Organizational prowess on the performance of organizations so that they are able to deal with any future developments and challenges, in addition to that this relationship supports the organization in achieving its desired goals so that it can deal with the competitive work environment by uncovering opportunities, self-development and innovation. We recommend the decision makers in the Jordanian Ministry focus on supporting human capital and following up on human resource management in addition to the need to strengthen the organizations marketing departments, as they are the main points of contact with the local community, apply modern electronic system in the application of organizational ingenuity so that we have higher quality results and faster.